2019
DOI: 10.1126/scisignal.aay0482
|View full text |Cite
|
Sign up to set email alerts
|

HIF-independent synthetic lethality between CDK4/6 inhibition and VHL loss across species

Abstract: Inactivation of the VHL tumor suppressor gene is the signature initiating event in clear cell renal cell carcinoma (ccRCC), the most common form of kidney cancer, and causes the accumulation of hypoxia-inducible factor 2α (HIF-2α). HIF-2α inhibitors are effective in some ccRCC cases, but both de novo and acquired resistance have been observed in the laboratory and in the clinic. Here, we identified synthetic lethality between decreased activity of cyclin-dependent kinases 4 and 6 (CDK4/6) and VHL inactivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…These multiple concentrations provided a broad picture of each drugs’ ability to block virus-induced CPE. For our screen, we repurposed a drug library that focused on cancer and metabolic targets, which previously had been used to examined drug sensitivities in cancer cells (Harris et al, 2019; Nicholson et al, 2019; Shu et al, 2020). The maximal inhibition of viral killing in cells (at any dose) was used to identify compounds as potential hits (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These multiple concentrations provided a broad picture of each drugs’ ability to block virus-induced CPE. For our screen, we repurposed a drug library that focused on cancer and metabolic targets, which previously had been used to examined drug sensitivities in cancer cells (Harris et al, 2019; Nicholson et al, 2019; Shu et al, 2020). The maximal inhibition of viral killing in cells (at any dose) was used to identify compounds as potential hits (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This enabled us to identify concentrations of compounds that inhibit virally-induced killing while also maintaining cell viability. Similar drug screening approaches have successfully identified selective vulnerabilities in cancer cells (Harris et al, 2019; Nicholson et al, 2019; Shu et al, 2020). To facilitate rapid screening, we tested the minimally pathogenic human coronavirus, OC43, which belongs to the same betacoronavirus genus as SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, candidate synthetic lethal (SL) partners have been identified through large-scale functional screens in cell lines using shRNA, CRISPR, or small molecule libraries. Using these approaches, a number of VHL SL interactions have been identified (19)(20)(21)(22)(23)(24). More recently, computational methods have been utilized to predict SL partners of somatic mutations in human cancer using genomic data sets (25,26).…”
mentioning
confidence: 99%
“…It is worth noting that the aforementioned drugs are directed against downstream effectors of VHL, hence, from an evolutionary point of view, there is a potential to better define the molecular target. Nicholson et al found that inhibiting the cyclin-dependent kinases CDK4 and CDK6 impaired tumor growth in VHL-deficient ccRCC regardless of HIF2α dependency [40]. Abemaciclib, a CDK4/6 and PIM1 kinase inhibitor is currently being tested in phase I trial in combination with sunitinib in metastatic RCC (NCT03905889).…”
Section: Targeting Trunk Mutationsmentioning
confidence: 99%